Lohia's quest for civil liberty: Court cases & judgments - Edited by Ali, Qurban; Reddy, B. Sudershan (Fwd.) (New Delhi Anamika Publishers, 2024)
It is of course well known that Rammanohar Lohia was arrested a total of twenty-five times, and out of that, he was arrested 12 times in independent India. it is also well known that he was a charismatic speaker, whose passion for social justice ignited the minds of many a young leader cutting his or her teeth in politics for the first time post independence, is also equally well known.
Keywords: Civil Liberty; Court Cases & Judgments